An investigation into the Assessment of Teachers' Questioning Techniques during Classroom Interactions - Ima Widyastuti; Adhi Kusuma; Linggar Nariratri; Barnica Mondal (Universitas Sarjanawiyata Tamansiswa, 2023)
The utilization of an interrogative approach is vital within the framework of educational progression. Participating in critical thinking can be advantageous for students as it helps stimulate their cognitive processes. The implementation of an interrogative strategy by the teacher is crucial in the classroom environment. Therefore, the purpose of this study was to ascertain the various questioning techniques used by an English vocational school teacher in Yogyakarta when interacting with Grade 10 students. Furthermore, the study aimed to ascertain the most commonly employed questioning technique as well as the least frequently used tactic by the teacher. The current study utilized a descriptive-qualitative research methodology. The data was obtained through the application of observation and interviews. The observation was to see the different types of inquiries presented and the general dynamics inside the classroom. Meanwhile, the interview was to obtain the teacher's viewpoint regarding the question methodology implemented in their teaching practices. The investigation has revealed several inquiry techniques that are dependent on the content of the inquiries. The strategies encompass probing questions (57.1%), factual questions (3.5%), divergent questions (3.5%), higher-order questions (14.2%), emotive questions (10.7%), and structuring questions (10.7%). The penetrating inquiry is the most successful approach for questioning, whereas the factual question and the divergent question are the least effective strategies.